Voluntary Product Accessibility Templates (VPAT) in Electronic Resources. Issue 3 (2nd October 2018) - Coghill, Jeffrey
Abstract: This article gives an overview of Voluntary Product Accessibility Templates (VPAT) as a standard by which libraries can certify the resources they provide can be accessed by users who may suffer from physical disabilities and vision and other impairments. This article also outlines the standards that are crucial to making the implementation of VPAT work. Furthermore, several examples are provided of how librarians may encounter difficult issues in working with vendors and users who need to access information in their daily routines.